STUDI PENGARUH TEMPERATUR KALSINASI TERHADAP KOMPOSISI FASA SERBUK ZnO YANG DISINTESIS MELALUI METODE SOL-GEL - Nurhayati, Nurhayati; Musyarofah, Musyarofah; Rahastama, Swastya; Shoodiqin, Dian Mart; Prayitno, Budi; Puspitasari, Nurrisma (Jurusan Fisika FMIPA Universitas Andalas, 2024)
This study investigated the effect of calcination temperature on the phase composition and crystal size of zinc oxide powders synthesised by the sol-gel method. Zn powder, HCl and NaOH were used as precursors in a multi-step process involving dissolution, titration, gel formation, leaching, drying and calcination at temperatures ranging from 300°C to 700°C for 2 hours. Rietveld analysis of X-ray diffraction (XRD) data using MAUD and Rietica software determined phase composition and crystal size. Initial analysis identified a single simonkolleite phase (Zn5(OH)8Cl2) prior to calcination, which disappeared at 500°C. Wurtzite (ZnO) appeared at 300°C, accompanied by secondary phases (NaCl and ZnCl2). The wurtzite content increased to 81.42 wt% at 700°C. Calcination temperature also influenced crystal size, which ranged from 27.34 nm to 110.61 nm for wurtzite at different temperatures. The results highlight the dynamic changes in phase composition and crystal size with different calcination temperatures, providing valuable insights into tailoring zinc oxide properties for various applications.